2021
DOI: 10.3389/fpubh.2021.601592
|View full text |Cite
|
Sign up to set email alerts
|

A Citywide ‘Virus Testing': Chinese Government's Response to Preventing and Controlling the Second Outbreak of SARS-CoV-2

Abstract: Containing the spread of SARS-CoV-2 is a daunting challenge globally. China, as well as a handful of other countries, has, for the most part, contained it by implementing strict policies. Wuhan's citywide virus-testing program presents a way forward in preventing and controlling the uncertainty, anxiety, instability and complexity it faces over the outbreak of SARS-CoV-2. Inarguably, the health crisis requires time-tested strategies and tactics for coordinating governments' and social entities' response to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is hypothesised that MT offers a major contribution to both surveillance and TTI and could thereby have a great impact on the spread of SARS-CoV-2. Experimental evidence is, however, limited to a setting with low incidence of SARS-CoV-2 [ 17 ]. An MT campaign in Slovakia showed a decrease in infection incidence, but their modelling suggested that the decrease did not exclusively result from MT and also required the impact of isolation and quarantine measures [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that MT offers a major contribution to both surveillance and TTI and could thereby have a great impact on the spread of SARS-CoV-2. Experimental evidence is, however, limited to a setting with low incidence of SARS-CoV-2 [ 17 ]. An MT campaign in Slovakia showed a decrease in infection incidence, but their modelling suggested that the decrease did not exclusively result from MT and also required the impact of isolation and quarantine measures [ 18 ].…”
Section: Discussionmentioning
confidence: 99%